Le temps scolaire et sa place dans la dynamique décisionnelle d’enseignantes pour prendre en compte la diversité des besoins des élèves - Léna Bergeron (Éducation et Socialisation)
A common way to accommodate the diversity of needs is to recognize and adjust to difficulties in the heat of the moment. Conversely, a more proactive way of intervention consists of following an intentional approach of teaching in order to anticipate and take the students’ needs into account. This approach places instructional design as an important lever in supporting the success of all students. The results of this collaborative research presented in this article will help understand the intellectual articulation (way of thinking) and the structural resources mobilized by teachers when planning their instructions in a context of diversity. Specifically, the focus is on the outcomes surrounding school time: its role in planning thinking, the dynamics involved in differentiating instruction, and the resulting issues.